Modus operandi of the Islamic money market: a proposal for holistic shariah adaptation - Olayemi, Abdul Azeez Maruf; Hasan, Aznan; Ibrahim, Uzaimah; Mahamood, Siti Mashitoh; Buang, Ahmad Hidayat (University of Sharjah, 2016)
This paper advocates a holistic Shariah adaptation of the modus operandi (operational model) of the Islamic interbank money market. It presents the reasons for the need for the substitution of the conventional methods of ‘tendering’, ‘auction’ and brokerage procedures in the market with the Shariah compliant methods of ‘al-Munaqasah,’ ‘al-Muzayadah’ and ‘al- Samsarah’ which are known and rooted in the Islamic law of transaction. It concluded that the adaptation of such procedures will lend more credence to the Islamic financial system that continues to receive criticism from various quarters. The study is a qualitative Shariah legal research. It is restricted to the jurisprudential analysis of the modus operandi of the market vis-a-vis the underpinning contracts of its procedure, in both the primary and the secondary stages of the markets.